(untitled) (Journal of Applied Learning and Teaching, 2022)
This paper aims to explore the role of virtual writing retreats in supporting postgraduate students and enhancing the quality of their learning experience in the COVID-19 higher education environment. Besides treating the writing retreats as sessions exclusively organized to foster writing productivity for established academics and doctoral students, the first lockdown in April 2020 demonstrated the various ways in which virtual writing retreats can support postgraduate students. The discussion draws on a five-month intense (auto-)ethnographic work involving 15 Master’s full-time students and Graduate Teaching Assistants from the London School of Economics and Political Science (United Kingdom). From April to September 2020, we ran 44 writing retreats on Zoom for a total of 352 hours. Responding to concepts of community of practice, social support, productivity and isolation/alienation, we have explored virtual writing retreats as a way to: 1) build a community, 2) create a virtual library, 3) combat isolation, and last but not least, 4) maintain productivity, in a context of crisis (and beyond). According to qualitative feedback and online participant observation, virtual writing retreats can create communities and generate emotional support—something that has fostered student communication and interaction despite physical distance and social constraints. Writing retreats can create a virtual library that helps maintain productivity, overcome writer’s block and enhance students’ learning experience. Based on this, we propose that the emotional support and productivity enhancement that emerged through and by virtual writing retreats, improve the quality of student learning experience—catering to both students’ wellbeing and academic performance.